Penggunaan Media Pembelajaran Powtoon Untuk Meningkatkan Hasil Belajar IPA Siswa SD Kelas V - Isnar, Mutma Inna (Universitas Negeri Makassar, 2025)
This research is motivated by problems that occur in learning in class V SD Inpres 10/73 Bajoe. The formulation of the problem in this study is First, how is the description of the results of learning science in grade V SD Inpres 10/73 Bajoe. Second, how to use Powtoon media in learning science for class V SD Inpres 10/73 Bajoe. This research is a classroom action research that aims to improve the learning outcomes of fifth grade students at SD Inpres 10/73 Bajoe in learning science using Powtoon learning media. The variables in this study were the Powtoon learning media (independent variable) and the science learning outcomes of fifth grade students at SD Inpres 10/73 Bajoe (dependent variable). This study uses a qualitative descriptive approach and uses data collection techniques through several methods, namely through tests, observations, interviews, and documentation. The results of the research conducted show that the use of Powtoon learning media in science learning in class V SD Inpres 10/73 Bajoe can improve student learning outcomes. Keywords: Powtoon learning media, learning outcomes, Science